2021
DOI: 10.1039/d1ja00041a
|View full text |Cite
|
Sign up to set email alerts
|

Determination of mercury (thimerosal) in vaccines using different oxidants and cold vapor atomic fluorescence spectrometry in dilute acids

Abstract: A simple and fast method was developed for the determination of thimerosal (TH) in vaccines based on decomposition through the action of oxidizing systems of the organic mercury compound to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…To some extent the reports of Gawor et al, 211 de Oliveira et al 50 and Vojtek et al 32 support Timerbaev's observations. Gawor et al 211 assert that 20-25% of all commercial pharmaceuticals are uorinated compounds, some F-containing compounds are harmless to health, but some are toxic and there are few available procedures for measuring concentrations of F in biological samples.…”
Section: Applications: Drugs and Pharmaceuticals Traditional Medicine...mentioning
confidence: 63%
See 3 more Smart Citations
“…To some extent the reports of Gawor et al, 211 de Oliveira et al 50 and Vojtek et al 32 support Timerbaev's observations. Gawor et al 211 assert that 20-25% of all commercial pharmaceuticals are uorinated compounds, some F-containing compounds are harmless to health, but some are toxic and there are few available procedures for measuring concentrations of F in biological samples.…”
Section: Applications: Drugs and Pharmaceuticals Traditional Medicine...mentioning
confidence: 63%
“…The study by Fu et al, 66 demonstrated greater sensitivity and lower background with this gas mixture compared with the more commonly used NH 3 /He gases. The LODs for Ti in human serum ranged from 0.78 ng L À1 for 48 Ti to 7.20 ng L À1 for less abundant 50 Ti and RSDs were between 2.0 and 4.2%. Results were veried by comparison with SF-ICP-MS measurements.…”
Section: Mass Spectrometrymentioning
confidence: 98%
See 2 more Smart Citations
“…A simple and rapid method for determining thimerosal (also known as thiomersal) in vaccines was developed by de Oliveira et al 81 It is added as a preservative, but being an organomercury compound, is toxic. The method of detection was cold vapour-atomic fluorescence spectrometry.…”
Section: Organic Chemical and Materialsmentioning
confidence: 99%